Evaluating the use of recycled sawdust in porous foam mortar for improved performance - Mydin Md Azree Othuman; Awoyera Paul O.; Abdullah Mohd Mustafa Al Bakri; Onyelowe Kennedy; Özkılıç Yasin Onuralp (Reviews on Advanced Materials Science)
The disposal of sawdust, a major byproduct of the timber and woodworking industries, presents a growing environmental concern due to its large volume and limited reuse options. Finding sustainable and rational approaches to repurpose this lignocellulosic waste is essential to reduce its environmental footprint. In this study, recycled sawdust was investigated as a partial replacement for fine sand in the production of porous foam mortar (FM), aiming to develop lightweight, eco-friendly construction materials. The experimental tests were focused on the physical (slump flow, setting time, density), mechanical (compression, flexural, splitting tensile, modulus of elasticity), durability (water absorption, porosity, permeability), and microstructural characteristics of the mortars. The FM mixes were produced using sawdust substitutes ranging from 0 to 25% by weight of fine sand. With a 25% substitution, the compressive strength dropped by 33.7%, from 9.8 MPa for the control mix (0% sawdust) to 6.5 MPa. Durability tests indicated a linear increase in water absorption and porosity with higher sawdust content. Despite these reductions, mixes with up to 15% sawdust substitution maintained acceptable mechanical and durability performance, demonstrating potential for non-structural applications. Further optimization of mix designs is suggested to improve performance characteristics, and this study emphasizes the dual benefits of reusing sawdust waste and encouraging sustainable construction methods.